Light-induced deffects in semiconductors - Morigaki, Kazuo; Hikita, Harumi; Ogihara Chisato (Singapore : Pan stanford, 2015)
This book covers electronic and structural properties of light-induced defects, light-induced defect creation processes, and related phenomena in crystalline, amorphous, and microcrystalline semiconductors. It provides a theoretical treatment of recombination-enhanced defect reaction in crystalline semiconductors, particularly GaAs and related materials. It also discusses experimental evidence for this phenomenon. Light-induced defect creation in hydrogenated amorphous silicon (a-Si:H) is described in more detail, including its mechanism and experimental results. The subjects treated by the book are important issues from the viewpoints of physics and applications.
Bibliography 173-194p.; Index 195-199p.
Keywords: Amorphous chalcogenides; Crystalline semiconductors; Hydrogenated microcrystalline silicon